2022
DOI: 10.1108/ohi-03-2022-0066
|View full text |Cite
|
Sign up to set email alerts
|

Potential for local communities in rural areas: sustainable development of prison siting in South Korea

Abstract: PurposeCorrectional facilities often constitute locally unwanted land use (LULUs), with local residents strongly demanding their relocation. Accordingly, the construction of correctional facilities is currently being promoted in regions that are far from city centres. Some local government officials consider relocating correctional facilities to rural areas as a golden opportunity to revitalise the economies of these areas. This paper focuses on the possibilities of local community participation in the sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The situation is similar to that in the developed world where in early 2009 it was estimated that 30 percent of the rural European population still had no broadband access. This gap has been effectively addressed in developed countries and that the most important aspect is not the connectivity but rather effective utilization of the deployed broadband connectivity to deliver acceptable user experience for it to be beneficial to communities and bridge the digital divide (Park et al, 2013). In their paper, Park et al (2013) try to pin point the utilization and sustainability of broadband adoption in rural areas in South Korea where they found that investment in human capital is more important than investing in infrastructure and that involvement of local communities in the connectivity initiatives made an impact.…”
Section: Global Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation is similar to that in the developed world where in early 2009 it was estimated that 30 percent of the rural European population still had no broadband access. This gap has been effectively addressed in developed countries and that the most important aspect is not the connectivity but rather effective utilization of the deployed broadband connectivity to deliver acceptable user experience for it to be beneficial to communities and bridge the digital divide (Park et al, 2013). In their paper, Park et al (2013) try to pin point the utilization and sustainability of broadband adoption in rural areas in South Korea where they found that investment in human capital is more important than investing in infrastructure and that involvement of local communities in the connectivity initiatives made an impact.…”
Section: Global Case Studiesmentioning
confidence: 99%
“…This gap has been effectively addressed in developed countries and that the most important aspect is not the connectivity but rather effective utilization of the deployed broadband connectivity to deliver acceptable user experience for it to be beneficial to communities and bridge the digital divide (Park et al, 2013). In their paper, Park et al (2013) try to pin point the utilization and sustainability of broadband adoption in rural areas in South Korea where they found that investment in human capital is more important than investing in infrastructure and that involvement of local communities in the connectivity initiatives made an impact. This is the case with many other countries like Tanzania, where there is a good number of initiatives to connect the rural areas but the impact is not seen.…”
Section: Global Case Studiesmentioning
confidence: 99%